Employee trust, commitment and firm reputation : the impact of internal communication and relationship management / Mohd Nasir Ibrahim - Ibrahim, Mohd Nasir (2014)
In building strong relationships with important publics, including employee, relationship management should be practiced. The feeling of trust between management and employee will be enhanced through richer communication that flows, and bringing results in stronger commitment to each other and to the organization itself. In addition, positive reputation for the firm lead from the feelings of trust and commitment, as employees is happy to be employed by the organization and in return, share their positive feelings with customers and other stakeholders. For the mutual benefit of an organization and its stakeholders, relationship management effort is thought to build a long term relationships. Employees' opinion will able to influence other stakeholders to have a more positive opinion about the reputation of the firm when they have been thought to have more credibility with the public as representatives of the organization with corporate communication efforts. The goal of rich communication with employees in engaging them prior to the organization 1s describe as an internal communication. The best method for building close relationships with employees is through face - to - face communication. The finding of this study collected from interview session, and questionnaires, it include the better understanding the role of rich communication in the perspective of relationship management with employees.